Nord America. - Weiland, C. F. (Carl Ferdinand), d. 1847. (Geograph: Instituts, 1837)
Map shows political territorial possessions in North America, individual states and territories of the United States extending north of the forty-eighth degree line of latitude. Texas and the Southwest are shown as part of Mexico. Alaska is shown as a Russian possession. Areas of Native American habitation and major cities are noted throughout. Inset: "Die Aleuten oder Catharina's Archip." [The Aleutian Islands or Catharine Archipelago]. Includes includes legend. Relief shown by hachures. Scale not given.